Ecotourism Development of Wanagiri Village through PKK Empowerment in Food Souvenir Processing of Taro, Marketing and Institutional Strengthening - Luh Suriati; I. Wayan Wesna Astara; Hanilyn Hidalgo; Amelia Nicolas; Mia Bella Fresnido; Rovina Kobun; Ketut Selamet; Ni Ketut Mardewi; Anak Agung Sagung Manik_Cindrawati; Ni LuhPutuSulis_Dewi; Ngakan P.G. Satria_Kesumayasa; I.WayanWidiantara_Putra; et al. (Archives of Current Research International, 2023)
The processing of innovative Food Souvenir products is currently growing rapidly, producing various processed products on the market. Village community empowerment aims to increase independence, knowledge, attitudes, and skills, so a mentoring program is needed according to needs. Wanagiri Village is a tourist destination village located in Sukasada District, Buleleng Regency. Wanagiri Village has a variety of natural potentials, one of which is taro tuber which has the potential to be developed. Taro Food Souvenir products are products that are in great demand by people throughout Bali. Taro Food Souvenir products have been produced and marketed by partners but not yet intensively, the packaging is not good and the marketing is not optimal. Partners want to improve the appearance of their products so that they have a long shelf life so that they can be economically independent. The solutions provided to solve the problems faced by partners are: providing appropriate technology for processing taro Food Souvenirs; packaging and labeling, marketing strategies, drafting rules for sharing of work and profit agreements between group members, and providing equipment assistance. The method used is active community participation and exploratory. Community service activities have been running smoothly. International community service regarding taro processing has a positive impact on society, especially economic empowerment, food diversification, and cultural preservation. recognizing that the community actively supports the success of this activity, respecting local traditions in a sustainable manner will benefit the community. The performance of food souvenir products will look more attractive and provide added value, which will have an impact on increasing income and people's welfare.